The American Review of Public Administration: A Biography. Issue 8 (November 2021) - DiPadova-Stocks, Laurie N.; Frederickson, H. George; Thomas, John Clayton
This article is an intellectual history of the noble endeavors and challenges involved in the creation and evolution of the American Review of Public Administration . It traces the journal's development from its beginning as the Midwest Review of Public Administration ( MRPA ) under the leadership of Park College professor Jerzy Hauptmann, a Polish intellectual who entered the United States at the end of World War II. Hauptmann launched MRPA with a regional focus, welcoming contributions from a variety of voices in public service–related occupations. A political scientist suspicious of the power of national governments, Hauptmann favored a less top-down regional approach. The article provides insights from the late 1960s into the growing field of public administration. Behind the scenes, the article chronicles the financial challenges, details of manuscript review processes, and more in an initially low-technology world. This history is also multi-institutional, detailing the journal's transfer from a small college to a team of scholars, including coauthor John Clayton Thomas, at the three public administration programs of the University of Missouri—in Columbia, Kansas City, and St. Louis. We are indebted to our now-departed colleague and coauthor, George Frederickson, for the idea of writing this article.